Replication of murine leukemia virus in bone marrow-derived lymphocytes. - Ruddle, N H (1976)
Murine lymphoid cells were infected in vitro with WN 1802 B, a naturally occurring murine leukemia virus isolated from the spleen of an 18-month-old BALB/c mouse. Normal spleen and bone marrow cells were more susceptible to infection than were cells prepared from thymus and lymph node. Spleen cells from athymic nu/nu mice also could be readily infected with virus. Permissive cells did not ingest iron readily infected with virus. Permissive cells did not ingest iron filings and did not adhere to plastic. Exogenous replication of murine leukemia virus was enhanced in spleen and lymph node cells treated with lipopolysaccharide, a bone marrow-derived lymphocyte mitogen. Conversely, cells treated with the thymus-derived lymphocyte cell mitogens, phytohemagglutinin and concanavalin A, were less capable of supporting murine leukemia virus replication. These studies suggest that the natural host for WN 1802 B is the bone marrow-derived lymphocyte.